2021
DOI: 10.15587/1729-4061.2021.248166
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aeration rate and method of process activation on the degree of purification of zinc-containing waste water by ferritization

Abstract: The aeration rate for the degree of purification of highly concentrated galvanic wastewater from zinc and ferrum ions was investigated using various activation methods. It is shown that the intensity of aeration has a significant effect on the quality of wastewater treatment and the characteristics of water treatment sludge. The efficiency of the use of an energy-saving method for activating the ferritization process with the use of electromagnetic pulses for the extraction of zinc ions from wastewater has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For example, during the chemical purification of washing water from galvanic production from heavy metals using alkaline precipitators, it was found that when Fe 3 + and/ or Al 3 + cations are present in wastewater or salts of these metals are used as coagulants, the residual content of heavy metal cations is significantly lower than those calculated from the solubility of the corresponding hydroxides. The process of formation of a precipitate with reduced solubility in the presence of Fe-ions was called "ferritization" [10][11][12] because heavy metal ferrites were found in the sediment. However, an analysis of published data shows that ferrites are characteristic of metals that easily form oxides in an aqueous medium (Zn, Cu).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the chemical purification of washing water from galvanic production from heavy metals using alkaline precipitators, it was found that when Fe 3 + and/ or Al 3 + cations are present in wastewater or salts of these metals are used as coagulants, the residual content of heavy metal cations is significantly lower than those calculated from the solubility of the corresponding hydroxides. The process of formation of a precipitate with reduced solubility in the presence of Fe-ions was called "ferritization" [10][11][12] because heavy metal ferrites were found in the sediment. However, an analysis of published data shows that ferrites are characteristic of metals that easily form oxides in an aqueous medium (Zn, Cu).…”
Section: Introductionmentioning
confidence: 99%